Rooting and shooting of Coffea canephora stem cuttings in response to clonal chamber conditions and rooting hormone in Ghana - Mohammed, Adams Latif; Kaddiri, Nasim Kumodu Nanbaala; Moro, Ali (Indonesian Coffee and Cocoa Research Institute, 2024)
Mass propagation of Coffea canephora through stem cuttings using various rooting hormones and clonal chambers is an innovative practice to hasten and mass produce planting materials of coffee for commercial production. The study was conducted to determine the rooting and shooting performance of C. canephoracuttings in response to rooting hormone and the clonal chamber using semihardwood stem cuttings. The experiment was laid out in a randomized complete block design (RCBD) with four treatments and replicated four times. The different treatments were: cuttings treated with hormone + propagated off clonal chambercondition), control (cuttings without hormonal treatment + propagated off clonal chamber condition), cuttings treated with hormone + propagated under clonal chamber condition), and cuttings without hormonal treatment + propagated under clonal chamber condition. Data collection started on the 8 th week after propagation and data were collected on leaf number, root number, root length and mortality of cuttings for a period of ten weeks. The study indicated that, the effect of rooting hormone on the number of roots, root length and cutting mortality was significant (pï‚£ 0.05) with the exception of the number of newly developed leaves. More so, the clonal chamber had a significant effect on the number of leaves, root number and root length as well as mortality (pï‚£ 0.05). The cuttings treated with rooting hormone propagated under clonal chamber conditions significantly improved the number of roots, root length, number of leaves with the least mortality. However, cuttings propagated off the clonal chamber conditions had the highest mortality, least root number, least root length and least leaf number. Therefore, it is recommended that the ideal treatment for C. canephora cuttings for mass propagation is to treat cuttings with rooting hormone and propagated under clonal chamber condition.